2003
DOI: 10.1107/s1600536803015101
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium 1,3,4,6-tetranitro-2,5-diazapentalene

Abstract: The structure of the ammonium salt of the dianion of 1,3,4,6‐tetra­nitro‐2,5‐di­aza­pentalene is reported, viz. 2NH4+·C6N6O82−. Only three atoms of the central 2,5‐di­aza­pentalene skeleton are unique, as the anion possesses 2/m symmetry. The ammonium cation forms strong hydrogen bonds to the aza N and nitro O atoms, forming a sheet in the ac plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…23,24 Apart from tetraphenylthieno(3,4-c)thiophene (IIe), [14][15][16] there is no experimental evidence for molecules IIb-d or their derivatives (though Closs et al reported 25 experimental evidence for II with X ) N) nor for IIIb-d, but crystal structures of potassium and ammonium salts of the dianion of 1,3,4,6tetranitro-2,5-diazapentalene have been published. 26,27 Compound VI, 7,8-diazapentalene, is the least stable diazapentalene isomer, nevertheless its derivatives were obtained and the crystal structures of nitro-substituted-7,8-diazapentalenes were reported. 28,29 The calculated structure of IId (Table 1) agrees well with the structure of IIe; the calculated ionization potential (6.35 eV, Table 3) is also in good agreement with experiment (6.19 eV 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Apart from tetraphenylthieno(3,4-c)thiophene (IIe), [14][15][16] there is no experimental evidence for molecules IIb-d or their derivatives (though Closs et al reported 25 experimental evidence for II with X ) N) nor for IIIb-d, but crystal structures of potassium and ammonium salts of the dianion of 1,3,4,6tetranitro-2,5-diazapentalene have been published. 26,27 Compound VI, 7,8-diazapentalene, is the least stable diazapentalene isomer, nevertheless its derivatives were obtained and the crystal structures of nitro-substituted-7,8-diazapentalenes were reported. 28,29 The calculated structure of IId (Table 1) agrees well with the structure of IIe; the calculated ionization potential (6.35 eV, Table 3) is also in good agreement with experiment (6.19 eV 16 ).…”
Section: Discussionmentioning
confidence: 99%